PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) PADA BPR RAM SEMARANG - MW Amelinda Eva E; Warsito Kawedar (Diponegoro Journal of Accounting, 2019)
The application of Good Corporate Governance is an issue that always improves and has effects towards economic system. To be able to compete with others nationally and internationally, a corporate is obligated to apply Good Corporate Governance. This application also ensures external parties that  corporate is free from frauds and authority abuse, which is corruption, collusion, nepotism, and financial statement manipulation.This research uses qualitative method with study case approach which is applied at one of Bank Perkreditan Rakyat (BPR) in Semarang. The purpose of this research is to understand how  Good Corporate Governance is applied in BPR and factors  enhancing or obstructing the success of Good Corporate Governance application. The data is obtained with in-depth interview with BPR RAM Semarang’s informers. The data is analyzed using descriptive analysis.The result shows Good Corporate Governance application consists of transparency, accountability, responsibility, independency, and fairness, at BPR RAM is well applied and has positive effects although there are obstacles that is discovered. The obstacles are there is less knowledge about Good Corporate Governance, individual heterogeneity and heterogeneity of habits.